Autophagy and Its Role in Protein Secretion: Implications for Cancer Therapy. (6th December 2018) - Cotzomi-Ortega, Israel; Aguilar-Alonso, Patricia; Reyes-Leyva, Julio; Maycotte, Paola
Abstract : Autophagy is a protein and organelle degradation pathway important for the maintenance of cytoplasmic homeostasis and for providing nutrients for survival in response to stress conditions. Recently, autophagy has been shown to be important for the secretion of diverse proteins involved in inflammation, intercellular signaling, and cancer progression. The role of autophagy in cancer depends on the stage of tumorigenesis, serving a tumor-suppressor role before transformation and a tumor-survival function once a tumor is established. We review recent evidence demonstrating the complexity of autophagy regulation during cancer, considering the interaction of autophagy with protein secretion pathways. Autophagy manipulation during cancer treatment is likely to affect protein secretion andinter-cellular signaling either to the neighboring cancer cells or to the antitumoral immune response. This will be an important consideration during cancer therapy since several clinical trials are trying to manipulate autophagy in combination with chemotherapy for the treatment of diverse types of cancers.